2014
DOI: 10.1016/j.carbon.2014.06.054
|View full text |Cite
|
Sign up to set email alerts
|

Control of the pore size distribution and its spatial homogeneity in particulate activated carbon

Abstract: There are circumstances where it is desirable to achieve a particular, optimal, pore size distribution (PSD) in a carbon, including in the molecular sieving, gas storage, CO 2 -capture and electrochemical energy storage.Activation protocols that cycle a carbon a number of times between a lowtemperature oxygen chemisorption process and a higher temperature pyrolysis process have been proposed as a means of yielding such desired PSDs. However, it is shown here that for PFA-based char particles of ~100 μ m in siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 25 publications
(33 reference statements)
2
25
0
Order By: Relevance
“…A poly(furfuryl alcohol)‐based carbon was used in this study as the adsorbent. The synthesis and activation procedures are described in detail elsewhere . In summary, distilled furfuryl alcohol was mixed at room temperature with oxalic acid as a mass ratio of 100:3.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A poly(furfuryl alcohol)‐based carbon was used in this study as the adsorbent. The synthesis and activation procedures are described in detail elsewhere . In summary, distilled furfuryl alcohol was mixed at room temperature with oxalic acid as a mass ratio of 100:3.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting chars were ground and sieved (100 μm), and then activated using repeated cycles of oxygen chemisorption (250 °C, 8 h) followed by desorption under argon (800 °C, 2 h). The sample used in the current work received nine such cycles, equivalent to 45 % burn‐off, resulting in a BET equivalent surface area of 950 m 2 g −1 and a pore volume of 0.37 cm 3 g −1 …”
Section: Methodsmentioning
confidence: 99%
“…In order to reduce as much as possible experimental uncertainties, the base carbon studied here, termed C45SCO 2 hereafter [44], was derived from a furfuryl alcohol (FA) precursor using a carefully controlled process.…”
Section: Sample Preparationmentioning
confidence: 99%
“…The full details of the synthesis process may be found elsewhere [54] Previous work by us [54,56] has demonstrated that both the porosity and chemistry, a summary of which may be found in Fig. 1 and Table 1, is homogeneous within the particles.…”
Section: Carbon Materialsmentioning
confidence: 99%